EVALUASI PROGRAM PENDIDIKAN INKLUSI DI SMK NEGERI 6 PADANG - Arlina, Arlina (TINGKAP, 2016)
ABSTRACTResults of previous studies indicated that implementation of inclusive education program is not in accordance with the standards that have been formulated. This article was written to describe the implementation of the inclusive education program at SMK N 6 Padang which includes the aspects of input (antecedent), the aspects of the process (transaction) and the aspects of the results (output). This research is a program evaluation with the model the Stake's Countenance. The data in this study were obtained from the principal, teachers, and students inclusions. Data were collected through interviews, observation, and documentation. Data were analyzed using data reduction, data presentation, and verification of data. The results of this study indicate that the aspect of the input is in compliance with the standard in terms of learners, but the aspects of curriculum, teaching, infrastructure, and funding have not met the standard. Besides, the aspect of the process, including planning and implementation, application of the principle of inclusive learning is still not optimal. In the aspect of output, the achievement of learning success is still lacking and the assessment of learning and the certificate is still equated with regular students.Keywords: Program Evaluation, Inclusive Education, input, process, output